Acehnese interference in students' spoken Arabic: A multi-level cross-linguistic analysis in an Indonesian Islamic boarding school - Maulana Ihsan Ahmad; Hisyam Zaini; Windi Alhafiza Rambe (Diwan: Jurnal Bahasa dan Sastra Arab, 2026)
Although numerous studies have examined Arabic language interference among Indonesian learners, detailed analyses integrating multiple linguistic levels within a single Acehnese-speaking institutional context remain a significant gap in the literature. This study addresses that gap by investigating cross-linguistic influence in students’ spoken Arabic at Dayah Babul Maghfirah, an Islamic boarding school in Aceh that formally enforces Arabic-only communication. Adopting a qualitative descriptive approach, the study analyzes naturally occurring oral interactions collected through non-participant observation over one week. Data were examined using Miles, Huberman, and Saldaña’s interactive model. The findings reveal systematic Acehnese interference across four linguistic levels: 1) phonological substitutions of marked Arabic consonants; 2) morphological projection of Acehnese particles and affixes; 3) syntactic transfer of Acehnese-dominant structural templates; and 4) lexical insertion of discourse markers and interjections. These patterns demonstrate that local linguistic repertoires remain structurally active even within immersion-oriented institutional settings, challenging assumptions that policy-driven environments suppress first-language influence. By providing a systematic multi-level mapping of interference within a single pesantren environment, this study contributes empirically to cross-linguistic influence research and extends Indonesian interference scholarship to an underrepresented regional context. The findings offer evidence-based insight for Arabic pedagogy in multilingual religious education settings where immersion policies coexist with deeply entrenched vernacular linguistic identities.